Hidden truths from Eden : esoteric readings of Genesis 1-3 - Scholz, Susanne, 1963-; Vander Stichele, Caroline (Atlanta : SBL Press, 2014)
"This unique volume features case studies and examples of diverse esoteric interpretive approaches and methodologies focusing on Genesis 1-3 and covering different periods from early Christian discourse through Zoharic, Kabbalistic and alchemical literature to modern and post-postmodern approaches"--
Part 1: Early Christian explorations. Adam, Eve, and the serpent in the acts of Andrew / Anna Rebecca Solevig -- Imperial propaganda in paradise? : Christ as eagle in the Apocryphon of John / Tuomas Rasimus -- A fitting portrait of God : Origen's interpretations of the "Garments of Skin" (Gen 3:21) / Peter W. Martens -- Part 2: Zoharic, Kabbalistic, and alchemical speculations. Bifurcating the androgyne and engendering sin : a Zoharic reading of Gen 1-3 / Elliot R. Wolfson -- The Genesis of Christian Kabbalah : early modern speculations on the work of creation / Peter J. Forshaw -- The mystery of Mysterium Magnum : Paracelsus's alchemical interpretation of creation in Philosophia ad Atheniensis and its early modern commentators / Georgiana (Jo) Hedesan -- Part 3: From modern to post-postmodern (re-)visions. Beyond postmodernism? : esoteric interpretations of Gen 1-3 / by E. Swedenborg, R. Steiner, and S.D. Fohr, Susanne Scholz -- Restoring a broken creation during times of Apocalypse : an essay on the analogical symbolism of fall and integrity in the metaphysics of Bila Hamvas (1897/1968) / Laszlo-Attila Hubbes -- The Bible and Africana esoterism : toward an architectonic for interdisciplinary study / Hugh R. Page Jr. -- Part 4: Responses. Strategies of esoteric exegesis / Elaine Pagels -- Esotericism and biblical interpretation / Samuel D. Fohr.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Bible. -- Criticism, interpretation, etc. -- History; Bible. -- Criticism, interpretation, etc., Jewish -- History; Creation -- Biblical teaching; RELIGION / Biblical Studies / Old Testament; Electronic books